Stability Constants of Ternary Complexes of Cd(II) with Itaconic Acid and Some Amino Acids: A Polarographic Approach - Karadia, Chanchal; Gupta, O.D. (Asian Journal of Chemistry, 2010)
A polarographic study of Cd(II) with some amino acids (alanine, phenylalanine and tyrosine) and phthalic acid have been carried out separately at ionic strength kept constant (μ = 1) by using KCl at 298 K. The stability constants of Cd(II) with itaconic acid and some amino acids were measured by the method of DeFord and Hume while the stability constants of mixed complexes have been evaluated by the method of Schaap & McMaster's. The reduction of the system in each case is reversible and diffusion control, involving two electrons. The statistical and electrostatic effects have also been discussed by using these stability constants. The mixing constants (Km) and stabilization constant (Ks) were measured for comparative study of simple and mixed ligand complexes.